Improved method of targeted user interface updates for enhancing the efficiency of web applications based on reactive streams and virtual DOM - M.V. Havatiuk; I.O. Saiapina (Технічна інженерія)
In today’s digital landscape, web applications have become an integral part of everyday life, enabling seamless access to information, services, and user interaction. Most modern applications are centered around the dynamic relationship between data and the user interface, which creates significant demands for efficiency in data processing and real-time interface updates. One of the key challenges lies in ensuring rapid, precise, and performance-optimized user interface rendering, especially in systems with frequently changing states. This article focuses on the development and implementation of an efficient update mechanism for graphical user interfaces, aimed at reducing computational overhead while maintaining interactivity and responsiveness. The proposed solution combines three core concepts: reactive programming, which allows automatic propagation of changes through the interface; virtual DOM, which minimizes direct manipulations with the real DOM and accelerates rendering; and a custom state management system designed to handle all application data updates in a centralized and consistent manner. Current practices for DOM manipulation are reviewed, including traditional direct updates and commonly used state managers such as Redux and Vuex. While these approaches are widely adopted, they can introduce unnecessary complexity and overhead in managing application state.